Molecular survey and genetic diversity of piroplasmids in equids from Midwestern Brazil - Schein,Fabio Bernardo (2018)
Abstract We evaluated the distribution of piroplasmids in equids from the Mato Grosso state in Midwestern Brazil using molecular methods and the interspecific genetic diversity. For this, 1,624 blood samples of equids from 973 farms were examined by PCR, using primer pairs that amplify a fragment of the genes rap-1 and ema-1 of Babesia caballi and Theileria equi, respectively. For molecular characterization and phylogenetic studies, 13 and 60 sequences of the rap-1 and ema-1 genes, respectively, were used to build a dendogram using maximum parsimony. B. caballi and T. equi were detected in 4.11% and 28.16% of the farms, respectively, and molecular prevalence was 2.74% for B. caballi and 25.91% for T. equi. The location of the farms and animals raised in the Pantanal ecoregion influence the probability of equids testing positive for B. caballi and T. equi . Moreover, age and herd purpose were variables significantly associated with T . equi infection. The sequences of B. caballi presented 1.95% intraspecific variability, contrasting with 2.99% in T. equi. Dendrograms for both species demonstrated the presence of subgroups with high values of support of branches. However, it is not possible to associate these groups with geographic origin and/or ecoregion.